Evaluating access: Comparing enrollment patterns in traditional versus multidisciplinary, project-based introductory statistics courses - Dierker, Lisa; Cooper, Jennifer; Selya, Arielle; Alexander, Jalen; Rose, Jennifer (Journal of Interdisciplinary Studies in Education, 2015)
To evaluate the potential impact of a multidisciplinary, project-based course on access to introductory statistics for underrepresented students, this article examines differences in demographic and disciplinary characteristics of students enrolling in a traditional introductory statistics course compared to the multidisciplinary, project-based course. Administrative data were based on individual student enrollment from fall semester 2009 and spring semester 2014. Results indicated that the project-based course provided an increased number of seats and enrollment from a large range of majors. Higher rates of under-represented students chose the project-based alternative over traditional introductory statistics. Though there was evidence that the project-based course also attracted students with lower Math achievement scores, a significant interaction between Math achievement and under-represented student (URM) status demonstrated that URM students selecting the project-based course had lower math achievement scores than URM students selecting the traditional course suggesting that prior math achievement.